Contribution de la télédétection et des systèmes d'information géographique à la prise en compte du risque de prolifération des Aedes dans les zones humides de Bizerte (Nord de la Tunisie) - Noura Brahmi; Abdessattar Hatira; Mohamed-Chedly Rabia (Physio-Géo)
The major objective of this research is to provide concrete solutions numerical cartography of the potential biotopes to larval lodgings of Aedes all around the wetlands of the area of Bizerte (Northern of Tunisia). These zones are presented in the form of favourable mediums for the proliferation of mosquitos which have a vectorial part in the transmission of much viral, microbial or parasitic affection (malaria, yellow fever, dengue…). These invasions set important problems of harmful effect that should be peculiarly considered and analysed if one wishes to find concrete remedies to stop them. To fight effectively against these Aedes, it is necessary to know thoroughly of their medium as well as their ecology. For this reason, we have established a data base integrated in a geographical information system (SIG) in order to define, to locate and to analyze, by superposing several layers of information related to the natural environment, the potential biotopes of proliferation of the larval lodgings of Aedes on the map of hazard. This constitutes a source of information necessary to specify the existing link between the environment and the harmful effect, the element considered to be vulnerable being the population. The map of risk of harmful effect, obtained by crossing hazard and vulnerability maps, shows three classes. The class where the risk is strong concerns Menzel Bourguiba, Menzel Jmil, Menzel Abderrahmen, Tinja and Ghar el Melh. The class with an average risk involves all the cities and the villages around the lake Ichkeul and its marshes.  The class with almost no risk covers the basin of the Sejnene wadi and the Garaât el Mabtouha.